1977
DOI: 10.1007/bf01946531
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependence of stress-induced hepatic autophagy

Abstract: In rats, restraint for 48 h elicits hepatic glycogen depletin, autophagy and other ultrastructural changes (e.g. mitochondrial enlargement and rough endoplasmic reticulum disorganization) associated with marked hypothermia. By restoring the body temperature of these animals, all the hepatocytic alterations are abolished.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

1978
1978
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…These results confirmed the impact of oxygen delivery during preservation on the maintenance of graft ultrastructural morphology. However, since mitochondria1 swelling increased during preservation in a time-dependent manner by each method, mitochondria may be strongly influenced not only by hypoxia but also by hypothermic stress as was seen in the liver model [13].…”
Section: Resultsmentioning
confidence: 92%
“…These results confirmed the impact of oxygen delivery during preservation on the maintenance of graft ultrastructural morphology. However, since mitochondria1 swelling increased during preservation in a time-dependent manner by each method, mitochondria may be strongly influenced not only by hypoxia but also by hypothermic stress as was seen in the liver model [13].…”
Section: Resultsmentioning
confidence: 92%
“…Immunohistochemistry showed the presence of a number of small accumulations of LC3 co-localized with cytochrome C in the cytoplasm of these hepatocytes (Panel C in S2 Fig). Salas et al found that hypothermia was a decisive element in the production of hepatic autophagy in rats [78,79]. In addition, the appearances of swollen mitochondria in the hepatocyte of mice under conditions of hypothermia have suggested that the damage to mitochondria is induced by the hypothermic condition itself [78].…”
Section: Discussionmentioning
confidence: 99%
“…Salas et al found that hypothermia was a decisive element in the production of hepatic autophagy in rats [78,79]. In addition, the appearances of swollen mitochondria in the hepatocyte of mice under conditions of hypothermia have suggested that the damage to mitochondria is induced by the hypothermic condition itself [78]. Extended times of HMP may also be subject to particular disadvantages and limitations with regard to endoplasmic stress [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the stress-induced changes in liver appear to be directly propor tional to the degree of hypothermia elicited by the stressing agents [Salas et al, 1977], Therefore, fasting a stressor also caused a significant depletion in hepatic glycogen content of rat. Rao [1979] observed a similar degree of depletion of muscle glycogen in starved lizards of young and old age groups.…”
Section: Resultsmentioning
confidence: 99%